The Influence Of Clinical Leadership And Self-Efficacy On Patient Safety Culture With Work Engagement As An Intervening Variable In Inpatient Nurses At X Hospital - Thea Tania; Intan Silviana Mustikawati; Ratna Indrawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is based on observation results which inform that there will be an increase in patient safety incidents in 2023 compared to 2022. The aim of this research is to empirically reveal the influence of clinical leadership and self-efficacy on patient safety culture with work engagement as an intervening variable. This type of research is quantitative with a cross sectional study design. The population used was 110 inpatient nurses. The sample calculation used the Slovin formula for an error rate of 5%, resulting in a sample size of 86 respondents. The data collection technique uses a questionnaire, and the analysis method uses three box method analysis and PLS-SEM with the help of the Smart-PLS program. The results of the analysis prove that clinical leadership and self-efficacy influence patient safety culture with work engagement as an intervening variable. Clinical leadership and self-efficacy have an influence on work engagement, clinical leadership, self-efficacy and work engagement have an influence on patient safety culture, and clinical leadership is the dominant variable capable of improving patient safety culture.